"Zwierzę - żywe tworzywo artysty?" Zapis debaty - fragmenty - Kubisz, Marzena; Wylężek, Ewa; Porwit, Tomasz; Stopel, Bartosz (Er(r)go. Teoria - Literatura - Kultura, 2014)
A transcription of a debate dedicated to artist's use of live animals as material for their work. The debate was held at the Gliwice Museum in Gliwice, Poland, on Oct. 12th, 2012.